Tingkat pengetahuan dokter umum mengenai bukti medis kekerasan seksual di RSUD se-Provinsi BALI tahun 2017 - I Gusti Ayu Agung Dwijayanti; Dudut Rustyadi; Kunthi Yulianti (DiscoverSys Inc., 2019)
Background: Sexual violence is a frequent criminal offense. Targets that become victims of the crimes can be women even today many occur in children. Medical evidence is the key to the proof of a case of sexual violence that is usually made by a forensic specialist. A general practitioner is expected to be able to examine the medical evidence of sexual violence considering the number of forensic specialists who are not comparable with the geographical area of Indonesia.Aim: The study aims to know the level of knowledge and relation between the variable of age, practice experience, and level of education related to the knowledge level of general practitioners about medical evidence of sexual violence.Method: This study is descriptive cross-sectional research located at Emergency Department all over General Hospital in Bali Province. The subject is general physician â‰¤60 years old. Data obtained use questionnaire containing a set of questions.Result: The results showed the general practitioner knowledge level about medical evidence of sexual violence was good. Of the 110 samples, 87.3% had a good level of knowledge, 11.8% was sufficient, and 0.9% had less knowledge level. One variable influenced the general physician's knowledge level was practical experience (p = 0.039). Moreover, the age (p = 0.908) did not have a significant relationship to the general practitioner knowledge level about medical evidence of sexual violence.Conclusion: It is essential that practical experience for a doctor's knowledge level about medical evidence of sexual violence is critically important.